Epidemiology of nosocomial bacteria resistant to antimicrobials (Colombia Medica, 2011)
Nosocomial infections are a major challenge for public health because of the high rates of morbidity and mortality generated. It was considered that the excessive or inappropriate use of antibiotics triggers the emergence of resistant strains. Among the clinically important bacteria that most commonly cause nososcomial infections, Gram positive multiresistant pathogens stand out such as methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus spp (VRE), and the Gram negative strains of Klebsiella pneumoniae, Escherichia coli, Pseudomonas spp. and Acinetobacter baumannii producing expanded spectrum b-lactamases (ESbL). This review describes the behavior of the main bacterial pathogens resistant to antibiotics that cause infections in Europe, United States, and Latin America, emphasizing studies of molecular epidemiology on a global scale, including the major epidemiological studies in Colombia. The genetic structure of S. aureus and Enterococcus spp strains shows a clonal characteristic favored by the predominance of a small number of clones with the capacity to spread globally, due probably to cross-infection. However, the introduction of MRSA strains from the community encourages genetic diversity, tending to establish a genetic polyclonal endemic structure in places like the United States. In Gram negative bacteria, the high genetic diversity among isolates, mainly in Latin American countries, indicates that the polyclonal spread is influenced by horizontal transfer of plasmids, by excessive exposure to antibiotics, and prolonged hospital stays. In Colombia, there is information on nosocomial resistant pathogens, but molecular epidemiological information is still scarce.